Systematic Review of Recent Developments Related to Microergonomics of Surgical Instruments - Abed, Rana Idan; Hamandi, Sadiq J.; Faraj, Moneer K. (Al-Nahrain Journal for Engineering Sciences, 2024)
Researches are now being conducted on redesign as well as micro ergonomic interventions. Most micro-surgical tool designs concentrate on the manipulation of targeted tissue instead of the surgeon's hand, and this presents a new research opportunity for better fitting the equipment to the surgeon's hand. So the objective is to examine the advancements made in the last few years and provide a framework for ergonomic intervention framework regarding manufacturing systems. With the use of words like ergonomic design, intervention, and evaluation," the titles and abstracts of ergonomics publications were filtered to find relevant research. The paper describes the way that the concept of micro-ergonomics can enhance the design of the micro-instruments. Finally, an application of a new surgical instrument is stated as a pen needle holder designed by SOLIDWORK 22 which creating a wide range of possible uses for futuristic technology. In future, neurosurgical equipment design will incorporate concepts from surgical tool design together with penization, microergonomics, and electronics.